PERAN KOMUNIKASI INTERPERSONAL DALAM MEMBANGUN MUTU LAYANAN DI SMP NURUL JADID PAITON PROBOLINGGO - Rahman, Ahmad Rifdur; Syafii, Imam; Rahman, Yudi Ardian (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
services at Nurul Jadid Junior High School. Open, transparent, and sustainable communication plays an important role in building trust between the school, parents, and the community. It also encourages increased parental participation in children's education and strengthens public support for school efforts to improve the quality of educational services. This study uses a qualitative approach with a case study type, involving the principal, vice principal for curriculum, teachers, and students as informants. The results of the study show that interpersonal communication has a strategic role, namely as a tool to provide a deep understanding of school policies and programs, provide constructive feedback, create effective collaboration between teachers and parents, and manage conflicts productively. These findings confirm that effective interpersonal communication not only improves relationships between stakeholders, but also contributes significantly to improving the quality of educational services in schools